A Comparative Study of Wildlife Law Awareness and Enforcement in Two Districts Administered under Two Distinct Regional States, Southern Ethiopia. Issue 4 (2nd October 2022) - Fekadu, Meharu; Girma, Zerihun; Mengesha, Girma; Shona, Edilu
Abstract: A study was conducted to assess the awareness of the local community about wildlife conservation law and the effectiveness of wildlife law enforcement in the Arbegona and Nensebo woredas (districts) administered under two regional states, in southern Ethiopia. Household surveys, key informant interviews, field observations and document reviews were used to collect data. In total, 185 households (89 from Arbegona and 96 from Nensebo) were randomly selected for the household survey. Thirty-four key informants were also selected from the two districts. There was a significant difference about wildlife law awareness among age class ( p  = 0.000) and educational level ( p  = 0.014). A majority of the households (43.8% and 51%) in Arbegona and Nensebo woredas, respectively, indicated that the condition of wildlife and forest resources declined due to a lack of awareness on their importance and the increased human and livestock populations. A lack of staff and funds, insufficient equipment and low support from the community and regulatory bodies contributed to inefficient law enforcement in both districts. In both study areas, there are many threats to wildlife, which include illegal hunting, the expansion of agricultural land, illegal settlements, tree cutting and illegal livestock grazing. From the findings of the study, it can be concluded that there is a greater degree of forest/wildlife resource overexploitation and law enforcement ineffectiveness in the Nensebo woreda, administered by Oromia Regional State, than in the Arbegona woreda, administered by Sidama Regional State. Generally, to sustain wildlife conservation there is a need to raise awareness among farmers about wildlife laws and conservation practice. Moreover, there is an urgent need to have a strong formal framework/standard guideline to establish effective wildlife law enforcement practices.